Cerebral Air Embolism Following the Removal of a Central Venous Catheter in the Absence of Intracardiac Right-to-Left Shunting: A Case Report. Issue 13 (April 2015) - Eum, Da Hae; Lee, Seung Hwan; Kim, Hyung Won; Jung, Myung Jae; Lee, Jae Gil
Abstract : Abstract: Air embolism following central venous catheter (CVC) removal is a relatively uncommon complication. Despite its rare occurrence, an air embolism can lead to serious outcomes. One of the most fatal complications is cerebral air embolism. We report a case of cerebral air embolism that occurred after the removal of a CVC in a patient with an underlying idiopathic pulmonary fibrosis, subcutaneous emphysema, pneumomediastinum, and a possible intrapulmonary shunt. Although the patient had a brief period of recovery, his condition deteriorated again, and retention of carbon dioxide was sustained due to aggravation of pneumonia. Despite full coverage of antibiotics and maximum care with the ventilator, the patient died about 5 weeks after the removal of the CVC. We suggest that strict compliance to protocols is required even while removing the catheter. Furthermore, additional caution to avoid air embolism is demanded in high-risk patients, such as in this case.